Integration of Local Wisdom in Low Carbon Development Policies and Industrial Downstreaming - Marhaeni Ria Siombo (Supremasi Hukum: Jurnal Penelitian Hukum, 2025)
As an implementation of Indonesia's commitment to implementing the 'Paris Agreement', the government has issued various policies related to reducing greenhouse gas emissions that cause climate change that threatens the lives of living things, including humans. Several government policies, such as carbon trading, carbon storage, energy transition, have been regulated in several legal products. Complex problems arise because at the same time Indonesia is experiencing social problems, a high number of job seekers, increasing unemployment rates and the need for efficient utilization of non-renewable natural resources (coal, nickel, tin, gold). So the government made an industrial downstream policy. All management processes from raw materials to finished goods ready for consumption domestically. Of course, many factories will be built, which will carry out the process of converting raw materials into ready-to-consume goods, which in the production process will produce greenhouse gas emissions, especially carbon dioxide (Co2). There is a commitment to carry out low-carbon development, but on the other hand there are socio-economic needs that must be met. To combine these two interests, the local wisdom of the community in its closeness to nature, in 'protecting, caring for and utilizing' natural resources wisely, can be a strengthening and supporting element for low-carbon development. The normative legal method is used in examining various legal products and other references. The conclusion or implication of this article is that socio-cultural aspects must be a concern in the implementation of development because the principle of sustainable development is to align economic, ecological and socio-cultural aspects to achieve the welfare of the Indonesian people.